Serum pepsinogen cut‐off values in Helicobacter pylori‐infected children - Fujiwara, Shin‐ichi; Konno, Mutsuko; Watanabe, Satoshi; Toita, Nariaki; Takahashi, Michiko (Pediatrics international, 2022)
Background The aim of this study was to evaluate the standard values for gender‐ and age‐stratified serum pepsinogen (sPG) in Helicobacter pylori (H. pylori) non‐infected children and to determine the optimal cut‐off values of sPG for predicting H. pylori‐infected gastritis in children. Methods A prospective study for determination of sPG levels was performed in children with epigastric pain who underwent esophagogastroduodenoscopy over the past 16 years. After excluding subjects diagnosed with inflammatory bowel diseases, eosinophilic gastrointestinal disorders, or immunoglobulin A vasculitis, the diagnosis of H. pylori infection was defined by positive tissue culture or concordant‐positive results for histology and the rapid urease test. Results A total of 405 subjects were diagnosed as being H. pylori‐infected (79) or non‐infected (326). In the H. pylori non‐infected group, there were no significant differences in sPG levels among age groups; males had higher sPG I and sPG II levels than females. In the H. pylori‐infected group, sPG I and sPG II levels were significantly higher and the sPG I/II ratio was lower than those in the non‐infected group. In receiver operating characteristics analyses in diagnosing H. pylori infection, the areas under the curves for sPG I, sPG II and sPG I/II ratio were 0.896, 0.980, and 0.946, respectively. The optimal cut‐off value of sPG II of ≥9.0 ng/mL was considered positive for H. pylori infection (sensitivity: 92.4%, specificity: 93.9%). Conclusions The optimal cut‐off value of sPG II of ≥9.0 ng/mL may be a good predictor of H. pylori‐infected gastritis in children.